The Geographic Effects of Monetary Policy Shocks - Herreño, Juan; Pedemonte, Mathieu (The Review of Economics and Statistics, 2025)
We estimate the effects of monetary policy shocks across local areas in the US and find substantial variation in their responses. There is a positive covariance of the price and employment effects of monetary policy across regions, and more sensitive regions are those with low per capita income. These patterns are consistent with New Keynesian models of a monetary union where regions have different shares of handto- mouth consumers. The model predicts that monetary policy shocks create large differences in consumption and real wages across space, and that heterogeneity across local areas amplifies the aggregate responses to shifts in monetary policy rates.